गिबि भारतनि जारिमिन - (:unkn) unknown (Bodo Sahitya Sabha, 2022)
"The book is a translation of ""The Penguin History of Early India: From the Origins to AD 1300"" by Romila Thapar into Bodo language."
Gibi Bharatni Jarimin: Sigangnifrai AD 1300 sim.
Keywords: Bodo; History; Bodo; Bodo